2018
DOI: 10.3390/su10051454
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Life-Cycle Environmental Performance of Buildings

Abstract: The work presented in this paper is part of a research project aiming for the development of a performance-based approach for sustainable design, focusing on the efficient use of natural resources over the lifetime of buildings. The proposed approach requires the set of benchmarks to provide a consistent and transparent yardstick for the environmental performance of buildings and to strive towards an effective reduction in the use of resources and relative environmental impacts in the building sector. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 24 publications
0
49
0
1
Order By: Relevance
“…Despite being a relatively young methodology in this field, the LCA may provide a solution to the environmental challenges currently affecting the sector. These include the significant consumption of energy and raw materials, solid waste management, and greenhouse gas emissions (GHGs) [3,14,[37][38][39][40][41][42], making this an essential instrument with a view to the future.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a relatively young methodology in this field, the LCA may provide a solution to the environmental challenges currently affecting the sector. These include the significant consumption of energy and raw materials, solid waste management, and greenhouse gas emissions (GHGs) [3,14,[37][38][39][40][41][42], making this an essential instrument with a view to the future.…”
Section: Introductionmentioning
confidence: 99%
“…At the end-of-life stage, the geopolymer part of the panel (i.e., HDG) could be recycled and used as a replacement of virgin aggregate in roadbed, while non-recyclable parts of the panel would be disposed at landfill [ 25 ]. There are no impacts associated with the demolition of the panels (i.e., module C1), since the demolition is done manually.…”
Section: Application Of the Lca Methodologymentioning
confidence: 99%
“…Therefore, the benefits and loads beyond the system boundary stage (i.e., module D), includes the impacts of the transport to the road construction site and the benefits (negative sign) due to the replacement of virgin material in the road construction. The transport distance to the road construction site has been set to 50 km, see Reference [ 25 ]. The secondary material (i.e., recycled geopolymer) does not have the same quality as the virgin material.…”
Section: Application Of the Lca Methodologymentioning
confidence: 99%
“…However, none of these projects was especially focused on internal insulation solutions, also aiming at developing "probabilistic" approaches for the assessment of their performance from energy, economic and environmental points of view, as made in the RIBuild project.With the growing demand in the energy and climate mitigation targets, the number of LCA studies in the building field increased significantly, as shown by the recent reviews reported in [19][20][21]. Several authors focused on the LCA of various types of building internal insulation systems [22][23][24], even if the LCA application of internal insulation solutions for historic buildings is limited to fewer studies [1,25,26].Moreover, there is an increasing trend to develop and apply "probabilistic" approaches to LCA analysis, in order to fully capture the inherent uncertainties related to data quality and calculation Sustainability 2020, 12, 1535 3 of 35 methods [27][28][29][30]. Indeed, neglecting uncertainties and variabilities of various life cycle parameters and scenarios may affect the results' reliability and robustness for final decisions.In the state of the art, several studies in the building field deal with "probabilistic" approaches to LCA [31][32][33][34].…”
mentioning
confidence: 99%
“…Moreover, there is an increasing trend to develop and apply "probabilistic" approaches to LCA analysis, in order to fully capture the inherent uncertainties related to data quality and calculation Sustainability 2020, 12, 1535 3 of 35 methods [27][28][29][30]. Indeed, neglecting uncertainties and variabilities of various life cycle parameters and scenarios may affect the results' reliability and robustness for final decisions.…”
mentioning
confidence: 99%